Development and Implementation of Augmented Reality Enhanced High-Fidelity Simulation for Recognition of Patient Decompensation. Issue 3 (June 2021) - Zackoff, Matthew W.; Cruse, Bradley; Sahay, Rashmi D.; Fei, Lin; Saupe, Jennifer; Schwartz, Jerome; Klein, Melissa; Geis, Gary L.; Tegtmeyer, Ken
Abstract : Introduction: Simulation is a core aspect of training and assessment; however, simulation laboratories are limited in their ability to visually represent mental, respiratory, and perfusion status. Augmented reality (AR) represents a potential adjunct to address this gap. Methods: A prospective, observational pilot of interprofessional simulation assessing a decompensating patient was conducted from April to June 2019. Teams completed 2 simulations: (1) traditional training (TT) using a manikin (Laerdal SimJunior) and (2) AR-enhanced training (ART) using a manikin plus an AR patient. The primary outcome was self-assessed effectiveness at the assessment of patient decompensation. Secondary outcomes were attitudes toward and adverse effects during the AR training. Results: Twenty-one simulation sessions included 84 participants in headsets. Participants reported improved ability to assess the patient's mental status, respiratory status, and perfusion status (all P < 0.0001) during ART in comparison to TT. Similar findings were noted for recognition of hypoxemia, shock, apnea, and decompensation (all P ⩽ 0.0003) but not for recognition of cardiac arrest ( P = 0.06). Most participants agreed or strongly agreed that ART accurately depicted a decompensating patient (89%), reinforced key components of the patient assessment (88%), and will impact how they care for patients (68%). Augmented reality–enhanced training was rated more effective than manikin training and standardized patients and equally as effective as bedside teaching. Conclusions: This novel application of AR to enhance the realism of manikin simulation demonstrated improvement in self-assessed recognition of patient decompensation. Augmented reality may represent a viable modality for increasing the clinical impact of training. Abstract : Supplemental digital content is available in the text.